Exploring the history and culture of main square los tupes with augmented reality in San Diego, Cesar (2023)
Augmented reality (AR) has gained popularity as a tool for exploring cultural heritage sites. This study investigates the use of AR technology to enhance the visitor experience at Plaza Principal Los Tupes in San Diego, Cesar. As an important cultural heritage site, the study aims to explore the potential of AR technology in providing visitors with an immersive and interactive experience of the site's history and culture. An AR application was developed, incorporating historical and cultural information about Plaza Principal Los Tupes, to offer visitors an interactive and educational experience. A user study was conducted to evaluate the effectiveness of the AR application in enhancing visitor experience. The results reveal that AR technology significantly enhances the visitor experience at cultural heritage sites, allowing for a deeper understanding of historical and cultural significance. The study demonstrates the potential of AR technology in increasing visitor engagement, accessibility, preservation of cultural heritage, and overall visitor satisfaction and revenue. However, challenges associated with AR technology usage are identified, emphasizing the need for further research to overcome these challenges and fully realize the potential of AR technology in the cultural heritage sector.